Adult women’s learning in higher education: A critical review of scholarship - Daniele D. Flannery; Elisabeth Hayes (Adult Education Research Conference, 1995)
An extensive search of major journals and data bases raises issues and concerns about the current knowledge of women’s learning. Articles on adult women’s learning in higher education were difficult to locate and limited in number. Scholarship often was based on questionable assumptions about women’s learning. Emerging themes about women’s learning need to be supported by further research.